Dynamics of Physicochemical Parameters as Indicator of Water Quality: A Study of Ogun River, Nigeria - O. B., Adestina; E. D., Paul; A. A., Nuhu; C. C., Onoyima; F. G., Okibe (Indonesian Journal of Chemical Analysis (IJCA), 2024)
Environmental pollution is increasingly becoming a major global problem. Surface water pollution impacts human life and the ecosystem, emphasizing the need for water quality assessment and monitoring. In this study, water Samples were collected in Ogun River for two years (twice a year) and analyzed for the physicochemical parameters using standard methods. The results show that there was spatial and seasonal variation in the water quality of the river. The physical parameters Turbidity, EC, and TDS had significant positive correlations with each other but correlated negatively with DO and pH. A significant positive correlation also existed between pH and DO (0.918). Cluster analysis grouped the parameters into three clusters, while the PCA yielded 2-components, which explained 85.61 % of the total variance in the data set. Component 1 accounts for 69.26 % of the total variance and has strong positive loadings for Turbidity, EC, and TDS and strong negative loadings for pH and DO. Component 2 accounts for 16.35 % of the total variance, with strong positive loading for BOD. The results indicate that factors that increase the Turbidity, EC, and TDS levels will decrease the levels of pH and DO while exerting a less significant effect on BOD. This study provides valuable insight into the changes and interactions of parameters that affect the water quality, which is crucial for the sustainability and quality management of the water system.